Industry 4.0 aimed at accounting system - Honková, Irena (Masarykova univerzita, 2018)
Industry 4.0 means a current trend of digitalisation and related automation of production and changes at the labour market brought together with the Industry 4.0. More and more internal as well as external integration occurs, more and more data is collected for analysis and decision making, top management requires access to data in real time, we transfer to unified protocols, the quantity of wireless communication devices grows and thus the level of isolation of company systems is considerably reduced. This text discusses the digitisation within the accounting sphere. With its case study it shows how the requirements on presentation and information sharing of accounting and taxation sphere change: options to send tax documents in electronic form, links to Internet banking, XML communication, Internet shops or accounting in mobile phones. This text aims to provide the view not only on the accounting software but also on work of book-keepers. Thus the text presents the view on the whole accounting system within the environment of Industry 4.0. The final part of this text discusses the readiness of companies to the Industry 4.0.
Průmysl 4.0 se zaměřením na účetní systém
Keywords: Industry 4.0; Průmysl 4.0